Improved Outcomes Associated with the use of Shock Protocols: Updates from the National Cardiogenic Shock Initiative. Issue 7 (25th April 2019) - Basir, Mir B.; Kapur, Navin K.; Patel, Kirit; Salam, Murad A.; Schreiber, Theodore; Kaki, Amir; Hanson, Ivan; Almany, Steve; Timmis, Steve; Dixon, Simon; Kolski, Brian; Todd, Josh; et al.
Abstract: Background: The National Cardiogenic Shock Initiative is a single‐arm, prospective, multicenter study to assess outcomes associated with early mechanical circulatory support (MCS) in patients presenting with acute myocardial infarction and cardiogenic shock (AMICS) treated with percutaneous coronary intervention (PCI). Methods: Between July 2016 and February 2019, 35 sites participated and enrolled into the study. All centers agreed to treat patients with AMICS using a standard protocol emphasizing invasive hemodynamic monitoring and rapid initiation of MCS. Inclusion and exclusion criteria mimicked those of the "SHOCK" trial with an additional exclusion criteria of intra‐aortic balloon pump counter‐pulsation prior to MCS. Results: A total of 171 consecutive patients were enrolled. Patients had an average age of 63 years, 77% were male, and 68% were admitted with AMICS. About 83% of patients were on vasopressors or inotropes, 20% had a witnessed out of hospital cardiac arrest, 29% had in‐hospital cardiac arrest, and 10% were under active cardiopulmonary resuscitation during MCS implantation. In accordance with the protocol, 74% of patients had MCS implanted prior to PCI. Right heart catheterization was performed in 92%. About 78% of patients presented with ST‐elevation myocardial infarction with average door to support times of 85 ± 63 min and door to balloon times of 87 ± 58 min. Survival to discharge was 72%. Creatinine ≥2, lactate >4, cardiac power output (CPO) <0.6 W, and age ≥ 70 years were predictors of mortality. Lactate and CPO measurements at 12–24 hr reliably predicted overall mortality postindex procedure. Conclusion: In contemporary practice, use of a shock protocol emphasizing best practices is associated with improved outcomes.